The Open Cryotop System Is Effective for the Simultaneous Vitrification of a Large Number of Porcine Embryos at Different Developmental Stages - Gonzalez-Plaza, Alejandro; Cambra, Josep M.; Parrilla, Inmaculada; Gil, Maria A.; Martinez, Emilio A.; Martinez, Cristina A.; Cuello, Cristina (Frontiers in Veterinary Science, 2022)
The Superfine Open Pulled Straw (SOPS) system is the most commonly used method for vitrification of pig embryos. However, this system only allows the vitrification of four to seven embryos per straw. In this study, we investigated the effectiveness of the open (OC) and closed (CC) Cryotop® systems to simultaneously vitrify a larger number of porcine embryos. Morulae, early blastocysts and full blastocysts were vitrified with the open Cryotop® (n=250; 20 embryos per device) system, the closed Cryotop® (n=158; 20 embryos per device) system and the traditional superfine open pulled straw (SOPS; n=241; 4-7 embryos per straw) method. Fresh embryos from each developmental stage constituted the control group (n=132). Data expressed as percentages were compared with the Fisher’s exact test. The Kruskal-Wallis test was used to analyze the effect of the different vitrification systems on the embryo quality parameters and two-by-two comparisons were accomplished with the Mann-Whitney U test. Differences were considered statistically significant when p<0.05. Vitrified and control embryos were incubated for 24 h and examined for viability and quality. At the warming step, the embryo recovery rate for the CC system was 51%, while all embryos were recovered when using OC and SOPS. There were no differences between the vitrification and control groups in the postwarming viability of full blastocysts. In contrast, morulae and early blastocysts that were vitrified-warmed with the SOPS system had lower viability (p<0.01) compared to those from the OC, CC and control groups. The embryonic viability was similar between the OC and control groups, regardless of the developmental stage considered. Moreover, the embryos from the OC group had comparable total cell number and cells from the inner cell mass and apoptotic index than the controls. In conclusion, the OC system is suitable for the simultaneous vitrification of 20 porcine embryos at different developmental stages and provides comparable viability and quality results to fresh embryos subjected to 24 h of in vitro culture.